Asymmetric Impact of the Tropical Pacific on Summertime Arctic Sea Ice Trends Under Increasing and Decreasing Greenhouse Gases - Eun‐Sook Heo; Soon‐Il An; Jongsoo Shin (Geophysical Research Letters)
Abstract It has been known that the tropical Pacific influences the Arctic through teleconnections but this relationship depends on the climate state. Here, we examine the influence of the tropical Pacific on summertime Arctic sea ice change under both increasing and decreasing CO2 concentrations using CESM1.2 model simulations. During global warming, the western tropical Pacific sea surface temperature (SST) warming induces a barotropic high pressure pattern in the central Arctic, leading to increased downward longwave radiation and enhanced sea ice loss. However, during global cooling, the teleconnection from the tropical Pacific weakens, reducing its impact on downward longwave radiation and sea ice recovery. This weakening of the relationship in the ramp‐down is attributed to a diminished local atmospheric meridional overturning circulation induced by the western tropical Pacific SST warming. Differences between ramp‐up and ramp‐down scenarios would enhance our understanding of the role of the tropical Pacific in future Arctic sea ice trends.